Design, Synthesis and Biological Evaluation of Peptidyl Epoxyketone Proteasome Inhibitors Composed of β‐amino Acids. (3rd June 2014) - Zhang, Jiankang; Han, Mengmeng; Ma, Xiaodong; Xu, Lei; Cao, Jiayi; Zhou, Yubo; Li, Jia; Liu, Tao; Hu, Yongzhou
<x xml:space="preserve">Abstract</x> A series of novel di‐ and tripeptidyl epoxyketone derivatives composed of β‐amino acids were designed, synthesized and evaluated for their proteasome inhibitory activities and anti‐proliferation activities against two multiple myeloma cell lines RPMI 8226 and NCI‐H929 and normal cells (peripheral blood mononucleated cells). Among these tested compounds, tripeptidyl analogues showed much more potent activities than dipeptides, and four tripeptidyl compounds exhibited proteasome inhibitory activities with IC50 values ranging from 0.97 ± 0.05 to 1.85 ± 0.11 μm. In addition, all the four compounds showed anti‐proliferation activities with IC50 values at low micromolar levels against two multiple myeloma cell lines and weak activities against normal cells. Furthermore, Western blot analysis was performed to verify the proteasome inhibition induced by compounds 21d and 21e. All the experimental results validated that the β‐amino acid building block has the potential for the development of proteasome inhibitors.